Comparison of Welch-Powell and Recursive Largest First Algorithm Implementation in Course Scheduling - Yehezkiel Victorious Ermanto; Yosefina Finsensia Riti (Institute of Computer Science (IOCS), 2022)
One of the important things to make for the continuity of a good activity is to create schedules, with the creation of a schedule, the activities carried out can be more organized or organized. However, if in putting together a scheduling need to be considered to avoid collisions between activities, this can be prevented by using algorithms in the creation of schedules such as welch-Powell algorithms and recursive largest first. Between the two algorithms, the author wants to compare which algorithms are appropriate to be used in the preparation of a schedule such as for lectures in the Informatics Study Program of Darma Cendika Catholic University for semester 2 and semester 4 where two courses have the same time in one day. From the research conducted obtained the results of welch-Powell algorithm faster in terms of time and more concise in terms of complexity compared to the algorithm recursive largest first and from the coloring of graphs conducted obtained chromatic numbers worth 2, which means in one day used 2 lecture halls based on the similarity of time between courses in semester 2 and semester 4, to prevent the impact of classroom time at the same time.